(untitled) (Informatica, 2024)
The purpose of this study is to improve the quality of tourism service through deep learning technology, and to conduct an empirical study. By comprehensively analyzing the challenges and key factors of tourism service quality as well as the application status of deep learning in the field of tourism, an optimization strategy of tourism service quality based on deep learning is designed, and experiments and results are analyzed. The research results show that the strategy has certain feasibility and potential effect, which can accurately analyze user comments and demands, and provide targeted suggestions for improvement. However, there are still some challenges in terms of data quality and model selection. This study provides a strategy based on deep learning for tourism service providers and researchers, and has certain guiding significance for improving the quality of tourism service.